The Influence Of Leadership Style And Financial Compensation On Permanent Performance Through Motivation As Intervening Variables In PT. Capella Medan - kevin; Sofiyan; Salman Faris; Alex Tribuana Sutanto (TRIGIN PUBLISHER, 2022)
This study aims to examine and analyze the effect of leadership style and financial compensation on the performance of permanent employees at PT. Capella Medan. The population of this study were 95 employees of PT. Capella Medan. Saturated sampling technique. The sample of this research is 95 employees of PT. Capella Medan. The data analysis tool uses SPSS 25 with path analysis. The results of the analysis show that the leadership style does not have a positive influence on the variable performance of permanent employees at PT. Capella Medan. Financial compensation has no positive and significant effect on employee performance at PT. Capella Medan. Leadership style has a significant positive effect on motivation at PT. Capella Medan. Financial compensation has a significant influence on motivation at PT. Capella Medan. Motivation has a positive and significant effect on the performance of permanent employees at PT. Capella Medan. There is no influence of motivational variables in mediating the influence of leadership style on the performance of permanent employees at PT. Capella Medan. It has no effect, this shows that there is no influence of motivational variables in mediating the effect of financial compensation on the performance of permanent employees at PT. Capella Medan